KOMUNIKASI INTERPERSONAL ANTAR SISWA DI SEKOLAH DAN IMPLIKASINYA TERHADAP PELAYANAN BIMBINGAN DAN KONSELING - Pratiwi, Srie Wahyuni; Sukma, Dina (Konselor, 2013)
Interpersonal communication is the process of face-to-face exchange of information between two or more persons in an interaction with the feedback response. The ground reality, many students still tend to unfavorable communicate Â interpersonal relationships between students and consequently less well established. This study aimed to describe the interpersonal communication between students in terms of attitudes of openness, empathy, being supportive, positive attitude and equality. The results reveal the interpersonal communication between students as a whole are in the good category.